Improving ice hockey slap shot analysis using three-dimensional optical motion capture: A pilot study determining the effects of a novel grip tape on slap shot performance - Frayne, R. J.; Dean, R. B.; Jenkyn, T. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
There have been significant improvements in ice hockey equipment technology within the last decade; however, little is known about how these improvements are affecting puck mechanics. The purpose of this study was to develop a testing protocol using three-dimensional motion capture to improve ice hockey shot analysis by providing additional information to traditional shot analysis techniques. Then, the feasibility of this protocol was tested by performing a pilot study that analyzes the effects of a new grip tape on slap shot performance. Four elite hockey players performed four slap shots in each of the four conditions: (1) bare hockey stick/normal hockey gloves, (2) traditional hockey tape stick/normal gloves, (3) Greptile™ tape stick/normal gloves and (4) Greptile™ tape stick/Greptile™ gloves. Reflective markers attached to the puck, stick and target were tracked by a three-dimensional optical motion capture system recording at 200 Hz. Linear and angular velocities of the puck, accuracy and puck topple were not different between condition 1 and the remaining three grip conditions; however, there were accuracy differences between conditions 1 and 3. In addition, there were no correlations between angular velocity and shot accuracy, and puck topple and shot accuracy. Due to the small sample size, the effects of Greptile™ tape on slap shot performance must be further tested in order to compare the four conditions with more advanced statistics; however, the developed research strategy, using three-dimensional motion analysis, provides an approach to researchers and companies that are interested in identifying the effects of new hockey equipment/technologies on slap shot performance.